Antibiotic resistance of Stenotrophomonas maltophilia strains isolated from captive snakes - Hejnar, P; Kolár, M; Sauer, P (Folia microbiologica, 2010)
The minimum inhibitory concentrations (MICs) of 24 antibiotics were determined for 45 Stenotrophomonas maltophilia strains by the microdilution method at 37 and 30 degrees C (after 24 h and 48 h of incubation). The isolates were obtained from mouth swabs and pus of 116 captive snakes whereas the identical strains (based on PFGE) of the same origin were discarded. At 37 degrees C, the isolates showed a low frequency of resistance to levofloxacin (0 and 8.9 % of resistant strains after 24 and 48 h, MICs(50) 0.5 and 1 mg/L, MICs(90) 1 and 2 mg/L) and cotrimoxazole (2.2 % of resistant strains for 24 and 48 h, MICs(50) 4 mg/L for both time periods, MICs(90) 4 and 8). At 30 degrees C, the most effective drugs were also cotrimoxazole (2.2 and 6.7 %, MICs(50) 4 and 8, MICs(90) 8 and 32) and levofloxacin (8.9 and 46.7 %, MICs(50) 1 and 2, MICs(90) 2 and 4). The isolates were either identically or more susceptible to antibiotics than strains acquired from patients hospitalized at Olomouc University Hospital (the same region) with the exception of ciprofloxacin, cefoperazone, cefoperazone/sulbactam and ceftazidime.
Keywords: gramnegativní bakteriální infekce; Drug Resistance, Bacterial; Snakes; Carrier State; hnisání; Gram-Negative Bacterial Infections; mikrobiální testy citlivosti; antibakteriální látky; Suppuration; ústa; Anti-Bacterial Agents; Mouth; Animals; přenašečství; Stenotrophomonas maltophilia; bakteriální léková rezistence; hadi; Microbial Sensitivity Tests; zvířata